2015
DOI: 10.1080/21553769.2015.1091386
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of mangrove plants: a review

Abstract: Diabetes mellitus is a heterogeneous group of metabolic disorders characterized by persistent hyperglycaemia and becoming a serious threat to mankind health in all parts of the world. Production of reactive oxygen species and disturbed capacity of antioxidant defence have been reported for enhanced production of free radicals in diabetic subjects. As oxidative stress is found to be a central event in the development of diabetic complications, hence antioxidants may play an important role in the improvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 46 publications
2
41
0
3
Order By: Relevance
“…The available literatures have reported that most of the Avicennia species have been traditionally used as a medicine for a wide array of diseases worldwide by the local communities inhabiting the mangrove forests (Bandaranayake 2002, Das et al 2016. From many of the ethnomedicinal uses of the genus, the widest applications have been in the treatment of rheumatism, pregnancy, ulcer and smallpox (Bandaranayake 2002).…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…The available literatures have reported that most of the Avicennia species have been traditionally used as a medicine for a wide array of diseases worldwide by the local communities inhabiting the mangrove forests (Bandaranayake 2002, Das et al 2016. From many of the ethnomedicinal uses of the genus, the widest applications have been in the treatment of rheumatism, pregnancy, ulcer and smallpox (Bandaranayake 2002).…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…Following it, the optimized sugar sources (glucose and xylose) along with bark extracts of X granatum with different concentrations (1, 3, and 5 mg/10 mL of sugar solution) were utilized for the growth of the three organisms over an incubation period from 0 to 72 hours. The ethanol bark extracts of X. granatum have been reported earlier for its potential to increase glucose uptake in yeast cell during the assessment of antidiabetic activity . The reason for such activity may be attributed to the fact that X. granatum plant being rich in polyphenols has prominent free radical scavenging potential that might play an important role in protecting yeast cells from osmotic stress allowing them to have prolonged growth period.…”
Section: Fermentation Of Grass Biomass For Bioethanol Productionmentioning
confidence: 99%
“…The ethanol bark extracts of X. granatum have been reported earlier for its potential to increase glucose uptake in yeast cell during the assessment of antidiabetic activity . The reason for such activity may be attributed to the fact that X. granatum plant being rich in polyphenols has prominent free radical scavenging potential that might play an important role in protecting yeast cells from osmotic stress allowing them to have prolonged growth period. In the third part, the optimized concentration of plant extract was used against a constant weight of glucose (3 g) and xylose (3 g), and subsequently the growth was observed for the same time period.…”
Section: Fermentation Of Grass Biomass For Bioethanol Productionmentioning
confidence: 99%
“…One of the most frequent effects of uncontrolled diabetes is raised blood glucose. It could lead to fatal damages to the blood vessels, nerves, eyes, kidneys and eventually the heart [1,2]. Diabetes is not only lethal but it is also the major cause of blindness, heart attacks, kidney failure, strokes, gangrene, and neuropathy especially for adults [3].…”
Section: Introductionmentioning
confidence: 99%